What Do Patients Want? Patient Preference in Wound Care - Corbett, Lisa Q. (Mary Ann Liebert, Inc., 2014)
Patient preferences are statements made or actions taken by consumers that reflect their desirability of a range of health options. The concept occupies an increasingly prominent place at the center of healthcare reform, and is connected to all aspects of healthcare, including discovery, research, delivery, outcome, and payment. Patient preference research has focused on shared decisions, decisional aids, and clinical practice guideline development, with limited study in acute and chronic wound care populations. The wound care community has focused primarily on patient focused symptoms and quality of life measurement. With increasing recognition of wound care as a medical specialty and as a public health concern that consumes extensive resources, attention to the preferences of end-users with wounds is necessary. This article will provide an overview of related patient-centered concepts and begin to establish a framework for consideration of patient preference in wound care.